Card Sort Untuk Meningkatkan Prestasi Belajar Pada Materi Konsumsi Makanan Minuman Halal - Siti Munawaroh (MGMP PAI SMP BINTAN, 2023)
This article focuses on the application of the Card Sort method to Islamic Religious Education subjects on Halal Food and Beverage Consumption. Subjects of Islamic Religious Education with the basic competencies of halal food and drink and staying away from haram are included in the moral aspect. Seeing the phenomenon of today's children is very concerning because there are some students who ignore Islamic religious law in choosing food and drink, so that in understanding the material of halal food and drink and staying away from what is haram is not optimal. So that the impact on decreased student achievement. By utilizing the card sort method, data is obtained that student achievement shows a significant increase, which is indicated by an increase in student learning completeness.